High expression of EPB41L5, an integral component of the Arf6-driven mesenchymal program, correlates with poor prognosis of squamous cell carcinoma of the tongue. Issue 1 (December 2016) - Otsuka, Yutaro; Sato, Hiroki; Oikawa, Tsukasa; Onodera, Yasuhito; Nam, Jin-Min; Hashimoto, Ari; Fukunaga, Kiyoshi; Hatanaka, Kanako; Hatanaka, Yutaka; Matsuno, Yoshihiro; Fukuda, Satoshi; Sabe, Hisataka
Abstract Background Squamous cell carcinoma of the tongue (tongue SCC) is a major subtype of head and neck squamous cell carcinoma (HNSCC), which is an intractable cancer under current therapeutics. ARF6 and its effector AMAP1 are often overexpressed in different types of cancers, such as breast cancer and renal cancer, and in these cancers, AMAP1 binds to EPB41L5 to promote invasion, metastasis, and drug resistance. EPB41L5 is a mesenchymal-specific protein, normally induced during epithelial-mesenchymal transition (EMT) to promote focal adhesion dynamics. Similarly to breast cancer and renal cancer, the acquisition of mesenchymal phenotypes is the key process that drives the malignancy of HNSCC. We previously showed that the overexpression of AMAP1 in tongue SCC is statistically correlated with the poor outcome of patients. In this study, we examined whether tongue SCC also expresses EPB41L5 at high levels. Results Immunohistochemical staining of clinical specimens of tongue SCC demonstrated that high expression levels of EPB41L5 statistically correlate with poor disease-free survival and poor overall survival rates of patients. The tongue SCC cell line SCC-9, which overexpress Arf6 and AMAP1, also expressed EPB41L5 at high levels to promote invasiveness, whereas the weakly invasive SCC-25 cells did not express EPB41L5 at notable levels. Among the different EMT-associated transcriptional factors, ZEB1 was previously found to be most crucial in inducing EPB41L5 in breast cancer and renal cancer. In contrast, expression levels ofZEB1 did not correlate with the expression levels ofEPB41L5 in tongue SCC, whereasKLF8 andFOXO3 levels showed positive correlations withEPB41L5 levels. Moreover, silencing of EPB41L5 only marginally improved the drug resistance of SCC-9 cells, even when coupled with ionizing radiation. Conclusion Our results indicate that activation of the cancer mesenchymal program in tongue SCC, which leads to EPB41L5 expression, closely correlates with the poor prognosis of patients. However, ZEB1 was not the major inducer of EPB41L5 in tongue SCC, unlike in breast cancer and renal cancer. Thus, processes that trigger the mesenchymal program of tongue SCC, which drives their malignancies, seem to be substantially different from those of other cancers.